2013
DOI: 10.1002/asna.201211751
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of solar‐type stellar winds

Abstract: By extending our self-consistent MHD simulations for the solar wind, we study the evolution of stellar winds of solar-type stars from early main sequence stage to red giant phase. Young solar-type stars are active and the mass loss rates are larger by up to ∼100 times than that of the present-day sun. We investigate how the stellar wind is affected when the magnetic field strength and fluctuation amplitude at the photosphere increase. While the mass loss rate sensitively depends on the input energy from the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This result also strongly depends on the exponent chosen in the (T, n) laws, and more generally on how the acceleration of stellar winds depends on stellar properties. We aim to develop more physically motivated model of stellar wind acceleration (in line with Cranmer & Saar 2011;Suzuki 2013), that should be coupled with dynamo theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result also strongly depends on the exponent chosen in the (T, n) laws, and more generally on how the acceleration of stellar winds depends on stellar properties. We aim to develop more physically motivated model of stellar wind acceleration (in line with Cranmer & Saar 2011;Suzuki 2013), that should be coupled with dynamo theory.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the solar wind, whose properties have been strongly constrained over the past 30 years, stellar winds remain difficult to observe. Wood et al (2005) have provided constraints on the mass loss of a dozen of solar-like stars, providing directions to transpose solar wind models in the stellar context (see Holzwarth & Jardine 2007;Cranmer & Saar 2011;Suzuki 2013). Our approach rely on the widely used polytropic wind model that can describe the acceleration of an outflow from a million Kelvin hot corona thanks to a modified adiabatic index γ close to unity (see, e.g.…”
Section: Numerical Simulation Of Stellar Wind Versus Age and Rotationmentioning
confidence: 99%
“…The wave energy dissipates mostly via viscosity owing to neutral-neutral collisions and resistivity caused by ion-neutral collisions. The effect of mode coupling of the conversion of energy from Alfvén waves into slow magneto-sonic waves has also been observed and described in 1-D MHD simulations of the solar chromosphere by Lau & Siregar (1996), Torkelsson & Boynton (1998), Ofman & Davila (1997), Airapetian et al (2000) and Suzuki (2013) in simulations of solar and stellar atmospheres and winds.…”
Section: Energy Dissipation Due To Alfvén Waves: a Source Of Chromospmentioning
confidence: 93%
“…Non-linear coupling of Alfvén waves excite magneto-sonic waves, which can eventually steepen into longitudinal waves that become damped by shock formation. Suzuki & Inutsuka (2005) and Suzuki (2007Suzuki ( , 2013 pursued non-linear 1.5-D MHD simulations of Alfvén wave propagation from solar and stellar photospheres into the corona. While their model does not account for cross-field gradients, they showed that non-linear Alfvén wave dissipation in the solar atmosphere can explain its thermodynamics due to the dissipation of compressible waves produced by mode coupling of non-linear Alfvén waves.…”
Section: Momentum Deposition By Alfvén Waves: Driving Winds From Coolmentioning
confidence: 99%
See 1 more Smart Citation